Pengabdian Purna Santri dalam Meningkatkan Kemampuan Mengajar Santri Pondok Pesantren Nurul Cholil Bangkalan - Abdullah Abdullah; Mundiro Lailatul Muawaroh (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2021)
In educational practice, not all educators are able, aware and able to complete their obligations. Likewise, not a few teachers are often accused of having problems if their students are underachieving. With the holding of post-santri service (duty teacher) in an instructive climate at the pesantren, it becomes an alternative in giving birth to competent santri in teaching and educating. This study aims to analyze the implementation of post- santri service in improving the teaching ability of the santri of pesantren Nurul Cholil Islamic Bangkalan. In this research, the writer uses a case study approach and qualitative research type. This study found that the implementation of the post-santri service at pesantren Nurul Cholil Bangkalan aims to help the santri have the provision, skills, in the teaching and learning process in the community. In addition, so that the santri have good morals and become educators with noble character. The pesantren establish relationships with the community through compulsory santri work programs in an effort to disseminate Islamic principles that are rahmatan lil alamin.